Home learning experiences through the COVID-19 pandemic - Sarah Cattan; Christine Farquharson; Sonya Krutikova; Angus Phimister; Adam Salisbury; Almudena Sevilla (Institute for Fiscal Studies (IFS), 2021)
The COVID-19 pandemic has dealt a monumental blow to the education of English school children. Over the past 18 months, English school pupils experienced two long periods of nationwide school closures. The first round of universal school closures lasted 10 weeks (from 23 March to 1 June 2020); some pupils were not able to return to school until the start of September that year. This unprecedented action was repeated at the start of 2021, with pupils across England sent home for 9 weeks (from 5 January to 8 March 2021). Even when schools were open outside these periods, in-school provision was hampered by social distancing protocols, staff shortages and self-isolation. There is growing evidence that disruption during the pandemic has undermined children's education and increased inequalities between those from disadvantaged backgrounds and their better-off peers. So far, most of the evidence focuses on the initial period of school closures in Spring 2020. But as teachers and pupils start a new academic year, understanding how children's experiences changed over the course of the pandemic - and how these experiences differed for those from different backgrounds - will be an important step in assessing the extent of learning loss, and what can be done to help pupils to catch up.
Keywords: 330; Fernunterricht; E-Learning; Lernen; Bildungsniveau; Lockdown; Coronavirus; England; Großbritannien